Adequacy of pain management among advanced cancer patients with solid tumors attending palliative care centers in Dar es Salaam - Judith Mwijage; Willbroad Kyejo; Davis Rubagumya; Thabit Kombo; Blessing Mathew; Faisal Hooda; Mandela Makakala; Eunice Pallangyo; Harrison Chuwa (BMC Cancer)
Abstract Background Cancer pain presents a universal challenge for patients and their families, significantly impacting quality of life. While observational studies suggest an increase in palliative care programs in Tanzania, the adequacy of pain control for cancer patients remains underexplored. Addressing this gap is crucial for enhancing patient well-being and care quality. Methodology This analytical cross-sectional study, conducted from October to December 2021 in Dar es Salaam, Tanzania, involved 332 advanced cancer patients with solid tumors from the Aga Khan Hospital and Ocean Road Cancer Institute. A structured, interviewer-administered questionnaire comprising demographic data and factors influencing cancer-related pain (CRP) management was utilized. Additionally, the Brief Pain Inventory Short Form (BPI-SF) assessed pain intensity and interference. Statistical analysis, including chi-square tests and logistic regression, was performed using SPSS version 25 to evaluate factors associated with adequate CRP management. Results Among 332 participants, 199 (59.9%) experienced adequate pain management, with prevalence notably higher among females, patients from Aga Khan Hospital, divorced, employed, and tertiary-educated individuals. Multivariable analysis identified sex, employment status, and education level as significant predictors of adequate pain management, with females having twice the likelihood of adequacy compared to males (OR: 1.96; 95%CI: 1.06–3.66; p = 0.033). Self-employed participants had significantly lower odds of adequate pain management compared to the employed (OR = 0.08; 95%CI: 0.01–0.33; p = 0.002), while unemployment was associated with a 91% lower likelihood of adequacy (OR = 0.09; 95%CI: 0.01–0.42; p = 0.006). Furthermore, individuals with primary education were 2.47 times more likely to report adequate pain management compared to those with nonformal education (OR: 2.47; 95%CI: 1.16–5.43; p = 0.021). Conclusion The study highlights inadequate CRP management in Tanzania and emphasizes the influence of patient-related factors such as sex, employment status, and education level. These findings underscore the importance of tailored interventions to address disparities and enhance pain management strategies for cancer patients. Efforts to improve CRP management should consider sociodemographic factors to optimize care delivery and alleviate patient suffering effectively.